ANALISIS STRATEGI BISNIS LOGISTICS & SUPPLY CHAIN SUKU CADANG TOYOTA PADA PT. HADJI KALLA - Muhammad Firdaus; Muhammad Yunus Amar; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
Business strategy is very important in developing and optimizing future business potential. The aim of this study is to understand the condition of business performance Logistics and Supply Chain Toyota Spare Parts at PT. Hadji Kalla and to measure also to determine the business strategy of Logistics and Supply Chain Toyota Spare Parts at PT. Hadji Kalla. The study applied qualitative and quantitative descriptive, which conducted at PT. Hadji Kalla for ± 2 Months. Analysis method used SWOT analysis & TOWS Balanced Scorecard. Data were applied in research consist of qualitative and quantitative. Primary and secondary were source data. The results of study shows that 1) The performance of business Logistics and Supply Chain Toyota Spare Parts at PT. Hadji Kalla has different distribution of each kind and type of cars. 2) SWOT analysis of fourth BSC perspective indicates dominant position of company at quadrant I than progressive action should be taken through utilization of internal strengths for reaching a big enough marketing opportunity. 3) The business strategy determination of 4th perspective BSC: finance that is management in new business selection can be immediately prepared and socialized to the whole organization; customer that is to rais customer touch point to the customer; internal business process that is technological innovation to in facing digital era; and learning and growing that is to strengthen the position company’s employee in prosperity and completion. From this is condition of business performance with SWOT & TOWS BSC analysis application can be mapping the position of company and giving the output strategy of the fourth company business perspectives.